Robot-Assisted Laparoscopic Surgery for Hysterectomy: A Systematic Review of Randomized Controlled Trials - Rizki Isnantono Prabowo; Jodii Arlan Kurnia (GLOBAL HEALTH SCIENCE GROUP, 2025)
Robot-assisted laparoscopic surgery (RALS) has emerged as an advancement in minimally invasive gynecology, particularly in hysterectomy for benign and oncologic indications. Compared with laparoscopy and laparotomy, RALS offers enhanced visualization, dexterity, and precision, though concerns remain regarding cost, operative time, and outcomes. This systematic review aimed to evaluate the efficacy and safety of RALS compared with conventional laparoscopy or laparotomy for hysterectomy, focusing on perioperative, oncologic, and patient-centered outcomes. Method: The review followed PRISMA 2020 guidelines. A database search of PubMed, ScienceDirect, and Taylor & Francis identified 752 records. After removal of duplicates and screening, 70 full-text articles were assessed, and 4 randomized controlled trials (RCTs) met the eligibility criteria and were included. Study selection involved independent screening by two reviewers, with disagreements resolved by consensus. Data extraction used a standardized template capturing study design, population characteristics, interventions, comparators, and outcomes. Given heterogeneity across studies, a narrative synthesis approach was applied. Four RCTs were included, encompassing benign hysterectomy, low-grade and high-risk endometrial cancer, and early-stage cervical cancer. RALS showed lower conversion rates and comparable complications. Operative times were longer, but perioperative outcomes were favorable. Long-term follow-up suggested improved survival in endometrial cancer, though findings remain inconsistent. Patient-reported outcomes were generally equivalent. RALS is a safe and effective alternative with selective advantages, though longer operative time and higher costs limit adoption. Further large-scale RCTs and cost-effectiveness studies are needed.